PENGARUH PENGGUNAAN MEDIA RUMAH PINTAR TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DIKELOMPOK BERMAIN AULIA KOTA PEKANBARU - Bety Hariani; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study Aims To Know How Big Effect Against Smart House Capabilities Know Concepts and Numbers Year In Playgroup (KB) Aulia Pekanbaru. This research Consists Of Two Variables: Smart Home Solutions and Capabilities Know the Numbers. Proposed hypothesis in this study are the following: There Influence Use of Media Smart House of the ability to know the concept Numbers Children aged 4-5 years in preschool Aulia a foot Umbrella District of Pekanbaru. The study involved 16 subjects, namely 5-6 years old. Methods of data collection in this study using experimental. Data analysis techniques used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos. The results showed no significant positive relationship between Smart House Capabilities Against Childhood recognize numbers 5-6 Years Playgroup Aulia In Pekanbaru. Based on the results of test results Know the difference Capabilities Concept and Numbers child after using the Media Smart House are 50.32% influence of smart home technique.Keywords: Smart House, Concepts and Numbers